BOOK REVIEWS (Journal of Finance, 1970)
Book reviewed in this article: The Economics of Labor Force Participation . By W illiam G. B owen and T. A ldrich F inegan . Errors in Provisional Estimates of Gross National Product . By R osanne C ole . Exit, Voice and Loyalty: Responses to Decline in Firms, Organizations, and States . By A lbert O. H irschman . Investment, Interest and Capital . By J. H irshleifer . Dating Postwar Business Cycles: Methods and Their Application to Western Germany, 1950–67 . By I lse M intz . The Economic and Financial System . By R ichard A. W ard . Investment Banking in America: A History . By V incent P. C arosso . Uncertainty and Estimation in Economics, Volume III 1 . By D. G. C hampernowne . Strategy for Financial Mobility . By G ordon D onaldson . Information for Decision Making: Quantitative and Behavioral Dimensions . Edited by A lfred R appaport . The Function and Analysis of Capital Market Rates . By J ames C. V an H orne . Money, Banking and Income: Theory and Policy . By P ham C hung . Men, Money and Policy: Essays in Honor of Karl R. Bopp . Edited by D avid P. E astburn . Home Mortgage Delinquency and Foreclosure . By J ohn P. H erzog and J ames S. E arley . Programmed Text in Money and Banking . By J ohn T. M asten and W. W arren H aynes . Introduction to Monetary Economics . By R obert E. W eintraub . The International Monetary Fund, 1945–1965 . By J. K eith H orsefield , M argaret G. de V ries , and others. Industrial Development Bond Financing: Business and Community Experiences and Opinions . A labama B usiness R esearch C ouncil , in cooperation with the Center for Business and Economic Research, College of Commerce and Business Administration. The Bureau of the Budget . By P ercival F lack B rundage . Value Added Tax (VAT ). A report by the N ational E conomic D evelopment O ffice .